Attitudes towards refugees: Introducing a short three‐dimensional scale. (31st March 2022) - Kotzur, Patrick F.; Friehs, Maria‐Therese; Schmidt, Peter; Wagner, Ulrich; Pötzschke, Steffen; Weiß, Bernd
Abstract: Many researchers subscribe to the three‐component conceptualization of attitudes, the idea that attitudes have cognitive, affective, and behavioural (intentional) components. Yet, these components are rarely considered simultaneously in scales, especially those measuring attitudes towards refugees. Moreover, it is debated how these components relate to one another. We present the development and validation of a six‐item short‐scale to measure attitudes towards refugees based on three surveys (Study 1: N = 330; Study 2a: N = 2, 083; Study 2b: N = 2, 174). We assessed the performance of this scale with respect to three rivalling attitude conceptualizations (one‐factor, three‐factor, and second‐order factor model). We found that a three‐factor or second‐order factor conceptualization fitted best to the data. The scale had excellent psychometric properties. We hope that our work stimulates a wave of relevant research on attitudes towards refugees that applies this scale, and contributes to the debate on the conceptualization of attitudes in general.